Synthesis and Characterisation of Super-Paramagnetic Iron Oxide Nanoparticles (SPIONs) for Minimising Aeromonas hydrophila Load from Freshwater - Kumar, Munish; Gupta, Gyandeep; Varghese, Tincy; Shankregowda, Aruna M; Srivastava, Prem P.; Bhushan, Shashi; Shukla, Satya Prakash; Krishna, Gopal; Gupta, Subodh (Current Nanoscience, 2022)
Background: The current study was conducted to prepare an efficient super-paramagnetic iron oxide nanoparticle (SPIONs) to remove Aeromonas hydrophila from water. Methods: The nanoparticles were synthesized by the co-precipitation method and characterized by DLS, UV-Vis spectrophotometer, FT-IR, XRD, FEG-TEM, and VSM analysis. Results and Discussion: The results showed that the synthesized SPIONs were having a size range of 8-12nm with magnetic property. Bacteria removal efficiency and antibacterial activity of SPIONs were assessed in sterile distilled water by adding different concentrations of SPIONs viz. 0, 6.25, 12.5, 25, 50, 100, 200, 500, and 1000μM with different initial bacterial loads viz. 1×103, 1×104, 1×105, 1×106, and 1×107 CFU mL−1 at different time intervals 15, 30, 45, and 60 min. At low bacterial load (1×103 to 1×105 CFU mL−1), 95 to 99.99% of bacteria were removed by low SPIONs concentration (6.25-100μM) by 15min which was increased up to 100% by 30min. However, at high bacterial load (1×106 to 1×107 CFU mL−1), more than 87 to 95% of bacteria were removed by the highest SPIONs concentration (1000μM) by 15min, which was increased above 93 to 99.99% by increasing the exposure time to 60min. At low bacterial load (1×103 to1×105 CFU mL−1), the effective concentration was 3.21 to 6.42μM at 15-60 min intervals. Meanwhile, the effective concentration at high bacterial load was 267.81 μM at 15min, which was decreased to 104.09 μM with increasing exposure time to 60min. Conclusion: Based on the results, it is concluded that the antibacterial effect against A. hydrophila depends on the concentration as well as the exposure time of SPIONs. A low concentration of SPIONs is sufficient to remove 100% of bacterial load in lower exposure time and increasing concentration of SPIONs increases the antibacterial effect. However, further research requires to find the safe concentration of SPIONs for using it as a novel antibacterial agent for the treatment of aeromonads disease in aquaculture.
Keywords: co-precipitation